1989
DOI: 10.1111/j.1530-0277.1989.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol on the Acoustic‐Phonetic Properties of Speech: Perceptual and Acoustic Analyses

Abstract: This report summarizes the results of a series of studies that examined the effects of alcohol on the acoustic-phonetic properties of speech. Audio recordings were made of male talkers producing lists of sentences under a sober condition and an intoxicated condition. These speech samples were then subjected to perceptual and acoustic analyses. In one perceptual experiment, listeners heard matched pairs of sentences from four talkers and were required to identify the sentence that was produced while the talker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 14 publications
3
41
0
2
Order By: Relevance
“…They also found a change in the long-term average spectrum in intoxicated speech. There was an increase in highfrequency energy, which may reflect, in addition to an increase in the harmonics-to-noise ratio, an increase in the unvoiced/ voiced ratio (the ratio of the number of frames classified as voiceless and the number of frames classified as voiced) after alcohol consumption [as reported by Pisoni and Martin, 1989]. Finally, all previous studies which included relevant measures have found that speaking rate decreases (segmental durations increase) after alcohol consumption.…”
Section: Previous Findings On Alcohol-impaired Speechmentioning
confidence: 90%
See 3 more Smart Citations
“…They also found a change in the long-term average spectrum in intoxicated speech. There was an increase in highfrequency energy, which may reflect, in addition to an increase in the harmonics-to-noise ratio, an increase in the unvoiced/ voiced ratio (the ratio of the number of frames classified as voiceless and the number of frames classified as voiced) after alcohol consumption [as reported by Pisoni and Martin, 1989]. Finally, all previous studies which included relevant measures have found that speaking rate decreases (segmental durations increase) after alcohol consumption.…”
Section: Previous Findings On Alcohol-impaired Speechmentioning
confidence: 90%
“…Trojan and Kryspin-Exner [1968] reported an increase in fundamental frequency (F 0 ). Pisoni and Martin [1989] found that F 0 decreased for some, but not all subjects. Klingholz et al [1988] also found a tendency for decreased F 0 .…”
Section: Previous Findings On Alcohol-impaired Speechmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the work of the present author, the relationships between speech and intoxication appeared to be that: 1) speaking fundamental frequency (SFF) level was often lowered and SFF variability sometimes increased, 2) speaking rate was reduced, 3) the number and length of speech pauses often increased and 4) speaking intensity levels sometimes were lowered (Chin/Pisoni 1996;Pisoni/Martin 1989). Again, however, virtually all of these alcohol-speech relationships were quite variable.…”
Section: Alcohol-speech Relationshipsmentioning
confidence: 99%